Pengaruh Pendekatan Content and Language Integrated Learning (CLIL) terhadap Keterampilan Menulis Narasi Siswa Kelas V di UPT SDN 131 Gresik - Erfania Erfania; Apri Irianto; Reza Rachmadtullah (Journal on Education, 2023)
This journal is written by a woman who feels compelled to share her knowledge with readers in the form of a written work. Students in groups feel restless and announce the "opening sentence" of the content within the narrative essay. Errors in capitalization, abbreviated sentence structures, punctuation usage, word choice not in accordance with standardized Indonesian, and the use of punctuation marks are observed. The wisdom gleaned from the test results obtained by students is only achievable by including information from events depicted in the illustrations. The author's intention in the narrative is not to create conflict, and no such conflict arises from the observations in this section. A one-group pretest-posttest design and quantitative descriptive sampling were applied for the pre-experimental research. Thirteen fifth-grade students at UPT SDN 131 Gresik participated as essay subjects. Three data collection methods were applied: tests, observations, and note-taking. The analysis process was carried out using statistical methods employing the t-test. This aligns with the research title, which focuses on the Influence of the Content and Language Integrated Learning (CLIL) Approach on the Narrative Writing Ability of Fifth-Grade Students at UPT SDN 131 Gresik, which is the topic of this paper. SPSS Version 26 was used for the Pretest and Posttest in the One Group Design.